Cutaneous Adverse Drug Reactions in Hospitalized HIV/AIDS Patients - Yusuf Wibisono; Indropo Agusni; Afif Nurul Hidayati; Rahmadewi Rahmadewi; Astindari Astindari; Septiana Septiana; Dwi Murtiastutik (Department of Dermatology and Venereology, Faculty of Medicine, Universitas Airlangga, 2021)
Background: Cutaneous adverse drug reaction (CADR) is the most common manifestation of drug hypersensitivity in human immunodeficiency virus (HIV), which presented as maculopapular rash. The incidence of CADR is found to be more common in untreated HIV patients, and the frequency is higher in severe immunodeficiency status. Early diagnosis and appropriate treatment give better outcomes. Purpose: To evaluate the incidence and management of CADR in HIV and acquired immune deficiency syndrome (AIDS) patients. Methods: A retrospective descriptive study of HIV/AIDS patients with CADR who were hospitalized at Intermediate Care and Infectious Disease Centre Dr. Soetomo General Academic Hospital. Result: There were more CADR cases in 2017, accounted 2.35% of the total Intermediate Care and Infectious Disease Centre RSUD Dr. Soetomo General Academic Teaching Hospital ward patients. There were more male patients (62.5%), with the most commonly found at the age of 25-44 years (64.3%), and which mostly (89.3%) originated from Surabaya. The most common diagnosis was morbiliform eruption (60.7%), main complaint was red spots all over the body (45%), all of which are obscure erythematous macules. The most common causes were Duviral + Neviral antiretroviral (46%) and the most common treatment was dexamethasone injection. Conclusion: The incidence of CADR increased in 2017. The most frequent manifestation was morbilliform eruption due to Duviral+Neviral as the first line ARV treatment. Skin management varies widely in form of topical, oral, and intravenous injection drugs, mostly using steroid class, dexamethasone intravenous injection in particular.